2020
DOI: 10.1038/s41598-020-68567-1
|View full text |Cite
|
Sign up to set email alerts
|

Translating GWAS-identified loci for cardiac rhythm and rate using an in vivo image- and CRISPR/Cas9-based approach

Abstract: A meta-analysis of genome-wide association studies (GWAS) identified eight loci that are associated with heart rate variability (HRV), but candidate genes in these loci remain uncharacterized. We developed an image-and CRISPR/Cas9-based pipeline to systematically characterize candidate genes for HRV in live zebrafish embryos. Nine zebrafish orthologues of six human candidate genes were targeted simultaneously in eggs from fish that transgenically express GFP on smooth muscle cells (Tg[acta2:GFP]), to visualize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…To select gRNAs for our experiments, we pre-screened 23 gRNAs with high in vivo on-target efficiency. These gRNAs target zebrafish orthologues of human genes in loci identified by genome-wide association studies (GWAS) for cardiometabolic risk factors and diseases 34 36 and have been used to examine the role of the candidate genes in cardiometabolic disorders 37 , 38 . We first used genome-wide Nano-OTS 33 to identify off-target Cas9 cleavage activity in vitro for all 23 gRNAs (Supplementary Tables S1 , S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To select gRNAs for our experiments, we pre-screened 23 gRNAs with high in vivo on-target efficiency. These gRNAs target zebrafish orthologues of human genes in loci identified by genome-wide association studies (GWAS) for cardiometabolic risk factors and diseases 34 36 and have been used to examine the role of the candidate genes in cardiometabolic disorders 37 , 38 . We first used genome-wide Nano-OTS 33 to identify off-target Cas9 cleavage activity in vitro for all 23 gRNAs (Supplementary Tables S1 , S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used long-read sequencing to examine on- and off-target genome editing outcomes, across multiple stages of development and across generations. Genome editing was accomplished using standard routines for germline editing at the single-cell stage, using gRNAs that have recently been used for functional studies of cardiometabolic diseases in zebrafish model systems 37 , 38 . This revealed insertions and deletions of sizes up to several kilobases, at on- and off-target sites, with a high degree of individual-level variation in genome editing outcomes both in the F0 and F1 generations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that compared to other regions of the heart, the zebrafish SAN overexpresses several signature mammalian pacemaker genes, including those encoding HCN and Ca 2+ - and K + -gated channels ( von der Heyde et al, 2020 ; Minhas et al, 2021 ). In the context of SAN function, it has also been shown that knock down of the large-conductance Ca 2+ -activated K + channel (K Ca 1.1) in zebrafish, which is strongly expressed in the human SAN, results in sinus bradycardia ( Pineda et al, 2021 ), so it may play an important role in zebrafish SAN automaticity through its contribution to repolarisation.…”
Section: Discussionmentioning
confidence: 99%
“…F0 mutagenesis screens are becoming more and more relevant [ 21 , 25 , 72 , 73 ], largely due to the improvements in CRISPR/Cas9 gene targeting efficiency by modification of the enzyme or promoting nuclear localization [ 31 ]. Overall, gene targeting in medaka using CRISPR/Cas9 has proven to be highly efficient, as shown by the prominent loss of GFP expression in gfp crispants when injected at the 1-cell stage ( Fig 1B and S1 Fig ) and the prominent bi-allelic mutagenesis as apparent by the loss of eye-pigmentation in the oca2 crispants ( Fig 1C and S2A Fig ).…”
Section: Discussionmentioning
confidence: 99%